Upgrading Recycled Paper Using Astragalus gossypinus Tragacanth Gum as a Bio-based Additive - Mehdi Rahmaninia; Yasin Rahmati; Mehdi Tabarsa (BioResources)
Using environmentally friendly additives has been considered widely in different industries, especially papermaking, which has a high dependency on additives. The current study focused on applying a plant-based gum obtained from Astragalus gossypinus (a well-known plant in some regions of the world, especially Iran) in the papermaking process. The gum characterization showed a high content (about 84%) of carbohydrates (mainly hemicellulose with xyloarabinan monomers in the main chain and about 8% of uronic acid in the side chains), low ash content (2.58%) and insignificant protein content. FTIR spectra confirmed the structural results. The weight average molecular weight (Mw) and polydispersity of tragacanth gum were 4867 × 103 g/mol and 1.423, respectively. Considering the mechanical strengths results, applying the gum in recycled pulp improved tensile, burst, bending, and tear indices significantly. Moreover, fines retention experienced a significant increment by applying up to 2% of the gum. The pulp drainage decreased consequently by increasing the dosage of gum. The FESEM images confirmed the higher retention and bonding in paper structure by applying the gum. The results seem to open a new door for the application of different plant gums as a green additive for papermaking industries.